Plasma fibronectin is a component of cryoglobulins from patients with connective tissue and other diseases. Issue 1 (February 1981) - Anderson, B; Rucker, M; Entwistle, R; Schmid, F R; Wood, G W
Abstract : Twenty-four washed cryoglobulin precipitates were examined for the presence of plasma fibronectin, immunoglobulins, complement components Clq and C3, and fibrinogen. Plasma fibronectin was detected in all preparations by immunodiffusion with antifibronectin serum, whereas the other components were found in some but not all of the cryoglobulins.